Magnetohydrodynamic flow and heat transfer of a Jeffrey fluid towards a stretching vertical surface - Ahmad, Kartini; Ishak, Anuar (Thermal Science, 2017)
This study investigates the steady-mixed convection boundary layer flow near a stagnation point that runs about a linearly stretched vertical surface filled with a Jeffery fluid in the presence of a transverse magnetic field. It is assumed that the external velocity impinges normally to the wall and the wall temperature varies linearly with the distance from the stagnation point. The governing partial differential equations that govern the fluid flow are transformed into a set of coupled ordinary differential equations, which are then solved numerically using a finite-difference scheme. The numerical results are presented for some values of parameters, namely the Deborah number γ, the Prandtl number Pr, the magnetic parameter M and the mixed convection parameter λ, for both assisting and opposing flows.